The Effect of Surface Finish and Fillet Design on Tie Rod Shaft Lifetime at Coal Mill Plant Operation - Alif Burhanuddin Yusuf Habibie; Januartha, Andrian Sagisky; Arifin, Fatahul; Bayumi Setiawan (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2023)
The tie rod shaft is one of the most essential parts in the coal grinder machine at the coal mill plant to support the roller grinder axial movement. Since the tie rod shaft receives the cyclic load constantly, the inappropriate design can cause the lifetime of the shaft to be short. The broken incidents of the tie rod shaft at coal mill the coal mill plant of PT X takes effect on the Steam and Power Supply to the ammonia and Urea Plant. This Research aims to analyze the abnormality on the tie rod shaft, which is always broken on the fillet section. The Stress concentration factor, Maximum Stress, and Surface roughness on the fillet section of the shaft have an extraordinary effect on the Fatigue lifetime. With the special tool assistant, the conventional lathe machine can compete with the CNC machine Quality to make Fillet contour as well as polished treatment and precise as the tool assistant can make the constant rotational movement produced by the human hand. The result showed that the tie rod shaft with 0.33 μm surface roughness level and fillet dimension strictly at 5mm could extend the lifetime of the tie rod shaft beyond the target after installed on the plant